Konsep Pendidikan Karakter Menurut Imam Al-Haddad dan Relevansinya dengan Pendidikan Karakter di Indonesia - Harani, Mitsalina Nadhil; Sholihah, Ela; Indrawati, Dewi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
The community needs special attention to improve in a better direction; significant efforts are required. The built actions are a form of improvement efforts to various problems in the world of education. Character building is seen as a solution to these problems. This study aims to describe conceptually Islamic character building in the millennial era. This study uses a descriptive qualitative approach. This type of research is library research (library research). The subject of this research is the thought of Imam Al-Haddad. The study results suggest that character building, according to Imam Al-Haddad, is a perspective through the approach of tasawuf moral. Sufism is a teaching that has developed since classical and modern in countries with the Syafi'i school of thought. Sufism moral orientation leads to comprehensive character improvement based on the Al-Qur'an and hadith. In Sufism, it contains the morals of students to Allah SWT, the morals of students to teachers, the morals of students to themselves, and the morals of students to fellow humans. According to Imam Al-Haddad, the conception of character building is related to the values ​​of character building. This linkage will strengthen the character values themselves, which students easily apply in studying or in their daily lives.